Collective land rights: an essential asset for Pastoral communities in order to sustain their livelihoods and the environment in the Andean Altiplano - Damonte, Gerardo (2017)
Considering communal or condominium land tenure regimes enable sustainable pastoral production systems, public policy should be re-oriented to support pastoralist families’ collective land right access.